Unusual complications after bariatric surgery gastric plication - Doležalová Kormanová, K; Fried, M (Rozhledy v chirurgii, 2019)
Laparoscopic gastric plication (LGCP) is a relatively new bariatric-metabolic operation. The greater gastric curvature is invaginated into the gastric lumen, resulting in a shape similar to that obtained after sleeve gastrectomy. In our paper, we report two interesting cases of patients with gastric plication who presented specific findings - food bezoar and gastric diverticulum. Case reports of bezoars after bariatric surgery are reported most commonly after gastric banding and gastric bypass surgery. Diverticulum of the gastric wall is a complication specific to LGCP when a part of the invaginated gastric wall is slipped between two sutures. A prompt endoscopic intervention is recommended to relieve the obstruction and, in case of diverticulum, to diagnose and manage it surgically.
Keywords: diverticulum; Weight Loss; bezoar; laparoscopic gastric plication; Gastrectomy; lidé; výsledek terapie; complications; Laparoscopy; gastrektomie; Postoperative Complications; bariatrická chirurgie; Humans; hmotnostní úbytek; bariatric surgery; Bariatric Surgery; laparoskopie; Treatment Outcome; pooperační komplikace; Obesity, Morbid; morbidní obezita